Intensity of low-latitude nighttime F-region ionospheric density irregularities observed by ROCSAT and ground-based GPS receivers in solar maximum. (February 2015) - Sun, Yang-Yi; Liu, Jann-Yenq; Chao, Chi-Kuang; Chen, Chia-Hung
Abstract: This study examines the global correlation between the instantaneous total amplitude of ion density fluctuations observed by ROCSAT and the phase fluctuation of the total electron content (TEC) recorded by worldwide ground-based Global Positioning System (GPS) receivers during the high solar activity period of March 1999–December 2002 for Kp <3. The Hilbert–Huang transform (HHT) is applied to compute the instantaneous total amplitude of ROCSAT ion densities. The event-based and climatological comparisons of the total amplitude and occurrence probability of irregularities observed by ROCSAT show that the total amplitude can reveal both the occurrence probability of irregularities and the associated intensity. The noise level of the total amplitude is about 10 3.5 (near 3000) ions/cm 3 . The high correlation (correlation coefficient=0.81) between the GPS TEC phase fluctuation index F P and instantaneous total amplitude of ROCSAT electron densities suggests that the total amplitude can be used to globally monitor the intensity of irregularities at equatorial and within the latitude belt of ±15°. The relationship between the ionospheric background ionization and the irregularity intensity is further investigated. Highlights: We propose the instantaneous total amplitude of ion density to study the irregularity intensity. 3000 ions/cm 3 can be the background noise level of the irregularity intensity at 600 km altitude. The ionospheric background ionization is important for the formation of irregularities. The GPS and ROCSAT observed irregularity intensities have high correlation at low latitude.